A comunicabilidade da interação do usuário idoso com o aplicativo WhatsApp - OLIVEIRA, Regina Mares de Souza (Universidade Federal do Pará, 2025)
The advances in digital technologies and the widespread use of smartphones have greatly changed the way people communicate, mainly through social platforms. At the same time, the sharp growth of the elderly population raises the question of the relationship of the elderly and the new digital media, especially with the Covid-19 pandemic that has conditioned social isolation. This research aims to investigate the communicability of the interaction of elderly users with the WhatsApp application. Methodologically, it began with a systematic review of the literature, later, a case study was conducted with a group of 10 elderly, applied the Communicability Evaluation Method of Semiotic Engineering with the objective of knowing and explaining the communicative problems of use and relating them to the characteristics of the elderly. The results indicated interaction problems related to the attribution of meaning, perception, recognition of icons; indicated the most frequent communicability ruptures; indicated low vision as the most common change of aging; presented reports of the experiences of use of the elderly and also regarding the satisfaction and classification of the service.